2001
DOI: 10.1002/kin.1028
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of solid‐state reactions toward consensus—Part I: Uncertainties, failures, and successes of conventional methods

Abstract: An account of conventional dynamic thermal analysis (TA) with respect to uncertainties, failures, successes, and limitations as applied to solid-state (s-s) processes is discussed. A review of some controversial aspects of TA is presented. The scope is to discuss in three parts the adequate understanding of TA and to open a controversy about the dynamic methods and about the necessity of stimulating a consensus between scientists for a better TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…The disagreement may be explained if we take into account that these authors obtained their data using conventional thermoanalytical methods (isothermal method), and it has been demonstrated [16][17][18][19][20] that under conventional experimental conditions a reaction is strongly modified by the experimental parameters. (i.e.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The disagreement may be explained if we take into account that these authors obtained their data using conventional thermoanalytical methods (isothermal method), and it has been demonstrated [16][17][18][19][20] that under conventional experimental conditions a reaction is strongly modified by the experimental parameters. (i.e.…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, a suitable method for controlling external parameters is needed, thus the controlled rate thermal analysis (CRTA) method [7] has been used in this kinetic study. CRTA is a temperature management method that maintains a constant reaction rate at a value previously selected by the user during the entire carbothermal reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Isoconversional methods allow researchers to distinguish between single‐step kinetics und multistage kinetics . Single‐step kinetics can be described well by Equation .…”
Section: Role Of Apparent Activation Energymentioning
confidence: 99%
“…Because the partial pressure of the gases is proportional to the rate, the reaction proceeds at a constant overall rate previously selected by the user, under a constant partial pressure of evolved gas. Previous works have demonstrated the efficiency of CRTA to control the influence of experimental factors [18][19][20]. This method has been previously used to control the texture and the structure for many materials [21][22][23] through kinetic control of the thermal reaction of their precursors, and it has been reported that CRTA has higher sensitivity and resolution than the conventional methods.…”
Section: Introductionmentioning
confidence: 98%